Placental glucose transporter 1 and 3 gene expression in Monochorionic twin pregnancies with selective fetal growth restriction - Yao-Lung Chang; An-Shine Chao; Shuenn-Dyh Chang; Po-Jen Cheng (BMC, 2021)
Abstract Background In monochorionic twin (MC) gestations with selective fetal growth restriction (FGR), the discordant fetal growth usually is due to unequal placental sharing. Glucose, which is essential for oxidative metabolism in the growing placenta and fetus, is transferred from maternal blood by facilitated carrier-mediated diffusion via glucose transporters (GLUTs). How the GLUTs expression varies in the two placenta territories manifests discordant perfusion in MC twin pregnancy with selective FGR is unknown. This study evaluates the human placental GLUT1 and GLUT3 gene expression in MC twin gestations with selective FGR. Methods MC twin pregnancy with selective FGR was defined as the presence of inter-twin birth weight discordance of > 25% and the smaller twin with a birth weight less than the 10th percentile in third trimester. Fetal umbilical artery Doppler was checked within 1 week before delivery in the two fetuses. An abnormal umbilical artery Doppler was defined as persistently absent or reverse end-diastolic flow (UA-AREDF). GLUT1, GLUT3 and HIF-1α gene expression were assayed in each twin's placental territories. The inter-twin placental gene expression ratio was calculated as the placenta GLUTs or HIF-1α expression level of the selective FGR twin divided by expression level of the appropriate-for-gestational-age (AGA) cotwin. Higher gene expression ratio means elevated gene expression in the selective FGR twin's placenta territory compared to AGA twin's placenta territory. Results 15 MC twin gestations with selective FGR including nine with normal (group 1) and six with abnormal selective FGR twin UA Doppler (group 2) were included into this study. The GLUT3 and HIF-1α gene expression are significantly elevated in selective FGR twin's placenta territory in group 2 twin pregnancies (mean gene expression ratio as 2.23 and 1.65, p values as 0.015 and 0.045, respectively), but not in in group 1 twin pregnancies. Conclusion The upregulation of placental GLUT3 gene expression in selective FGR fetus with abnormal UA Doppler may be due to hypo-perfusion which is mediated by up -regulation of HIF-1α gene expression.